Comparative Study on Stable Isotopes of Different Occurrence Waters in China Southern Taihangshan Mountainous Region in Spring Season - Ye Liu, Chengyuan Hao, Wenjing Liu, Haitao Zhang, Mingyue Kou (Forest Chemicals Review, 1970)
Environmental isotope characteristics of different occurrence waters are the main basis for the application of stable isotope technique to regional water cycle. Based on detection data of 2020 by L2130-i liquid water/water vapor isotope analyzer, this study analysed stable isotopes composition characteristics of six kinds of water samples at the Piedmont Alluvial Plain of China Southern Taihangshan Mountainous in spring and the water phase transition relationship indicated by them. The results show that the stable isotope values of different occurrence waters are as follows, atmospheric precipitation, lake water, artificial river water, natural river water, reservoir water, and groundwater. Among them, the atmospheric precipitation is similar to the lake water while the reservoir water is close to the groundwater. The lakes in study area are relatively wide and closed in the water surface and have undergone a long period of surface evaporation fractionation in both winter and spring, which constitutes the main source of atmospheric precipitation. So the heavy isotopes of both atmospheric precipitation and lake water are more relatively enriched. The water in reservoir is mainly replenished by groundwater and little from other sources, which resulted to that the heavy isotopes of both reservoir water and groundwater were depleted obviously. These conclusions not only revealed the stable isotopic environmental characteristics of different occurrence waters in spring, but also provided stable isotopic evidences for regional water cycle.